Enhancing Students’ Understanding of Online Game Dangers through Information Services - Pratiwi, Wirna; Chalidaziah, Wan; Surya, Dedy (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2024)
The increasing prevalence of online game addiction among adolescents has become a serious concern due to its negative impact on students’ academic balance and mental health. This study aimed to examine the effectiveness of information services in improving students’ understanding of the risks associated with online gaming at SMA Negeri 1 Kejuruan Muda, Aceh Tamiang. A quantitative experimental approach was employed using a one-group pretest–posttest design. The participants consisted of 144 students selected through simple random sampling. Data were collected through questionnaires and systematic observations. The questionnaire was administered in three stages: an initial survey to identify students’ involvement in online gaming, a pretest to assess their baseline understanding of online gaming risks, and a posttest to measure changes in understanding following the implementation of the information service. Data analysis was conducted using descriptive and inferential statistical techniques to determine the effectiveness of the intervention. The results indicated a significant improvement in students’ understanding of the dangers of online gaming after receiving the information service. Comparisons between pretest and posttest scores demonstrated increased awareness of the negative consequences of online gaming, including addiction, health problems, declining academic performance, and changes in social behavior. Observational findings further revealed higher student engagement and improved self-regulation in managing gaming time. These findings confirm that information services are an effective strategy for enhancing students’ understanding of online game hazards and should be integrated into school guidance and counseling programs.